Development of a Closed-Loop Power Control for a Dynamic Interphase Power Flow Controller Based on a Fundamental Component Model - Ebner, Guenter; Trunk, Kai; Herold, Gerhard (7th IASTED International Conference on Power and Energy Systems, 2007)
This paper describes the development of a closed-loop power control for a Dynamic Interphase Power Flow Conroller (DIPFC). A DIPFC is a thyristor switched device within the FACTS family. In the following analysis the DIPFC is connected in series to a transmission line which links up two power grids in order to have an effect on the transmitted active- and reactive power. In [1] it was pointed out that under certain neglects the effects of the DIPFC on the electric circuit can be expressed by fundamental component susceptances of the thyristor switched modules. Another previous research project [2] demonstrated that a DIPFC device makes it possible to control the active- and reactive-power flow independently from each other. This paper in hand shows the development of a closed-loop power control for a DIPFC with two controlled modules in order to realize the above mentioned possibility.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.leen.develo
Keywords: DIPFC; FACTS; IPC; IPFC; Power transmission